2012
DOI: 10.1007/s13580-012-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of secondary-lateral branch removal during watermelon production

Abstract: The cultural practice of removal of the secondary-lateral branch of watermelon during the production in greenhouse requires intensive input of human labor. Secondary-lateral branch removal practices were examined in horizontally trained two watermelon cultivars (Citrullus lanatus), 'Sambock-gul' and 'Speed-honey' to determine the comparative differences in labor input as well as to understand their impact on plant and fruit growth and fruit sugar accumulation. Two experiments were conducted. Experiment 1 consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Active leaves on the secondary-lateral branch seemed to be a competing sink with fruit, which led to a slower fruit growth during fruit development, as shown in both the present study ( Fig. 2A) and our previous study (Choi et al, 2012). However, the slower fruit growth caught up around 3 weeks after pollination and there was no difference in final fruit weight between two treatments at 5 weeks after pollination (Fig.…”
Section: C 2c-1supporting
confidence: 84%
See 1 more Smart Citation
“…Active leaves on the secondary-lateral branch seemed to be a competing sink with fruit, which led to a slower fruit growth during fruit development, as shown in both the present study ( Fig. 2A) and our previous study (Choi et al, 2012). However, the slower fruit growth caught up around 3 weeks after pollination and there was no difference in final fruit weight between two treatments at 5 weeks after pollination (Fig.…”
Section: C 2c-1supporting
confidence: 84%
“…However, Hubbard et al (1990) reported that when 50% of plant leaves were removed 28 days before harvest, a significant reduction in the soluble solid content of fruit was observed. Our previous study examined secondary-lateral branch removal to determine the comparative differences in labor input as well as its impact on plant and fruit growth and fruit sugar accumulation (Choi et al, 2012). The results showed that during the fruit ripening period, younger and developing leaves on secondary-lateral branches had a higher growth rate and higher photosynthetic activity than leaves on lateral branches did.…”
Section: Introductionmentioning
confidence: 99%
“…In Cucurbitaceae crops, cultivators may remove secondary-lateral branches to prevent the production of too many female flowers [54]. This may be particularly relevant to watermelon management, where this practice may ensure bigger fruit, especially considering that people usually keep only one fruit per plant [55,56]. An increased production of female flowers may later require more resources for increased fruit and seed production.…”
Section: Discussionmentioning
confidence: 99%
“…All fruits were harvested when they reached a length of 18 cm or one month after the end of the pollination treatments, whichever indicated maturity, beyond this length, or after one month when fruits began to turn yellow and decay [55]. All the fruits were recorded after the pollination experiment.…”
Section: Fruit Productionmentioning
confidence: 99%
“…In Cucurbitaceae crops, cultivators may remove secondary-lateral branches to prevent the production of too many female flowers [47]. This may be particularly relevant to watermelon management, where this practice may ensure bigger fruit, especially considering that people usually keep only one fruit per plant [48,49]. An increased production of female flowers may later require more resources for increased fruit and seed production.…”
Section: Discussionmentioning
confidence: 99%